2020
DOI: 10.3892/etm.2020.8625
|View full text |Cite
|
Sign up to set email alerts
|

Protective effect of emodin on intestinal epithelial tight junction barrier integrity in rats with sepsis induced by cecal ligation and puncture

Abstract: Αbstract. The present study investigated the protective effects of emodin on intestinal epithelial tight junction (TJ) barrier integrity in cecal ligation and puncture (CLP)-induced septic rats and its possible mechanisms of action. Healthy male Sprague-Dawley rats were randomly divided into three groups (n=20 per group): Sham group, CLP group and CLP + emodin group. Animals were sacrificed at 12 and 24 h after the model was established. Abdominal aortic blood and specimens of the ileum were harvested for anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 58 publications
(57 reference statements)
1
15
0
Order By: Relevance
“…The MG and CG groups were administered saline and 0.13 mg/kg ciprofloxacin, respectively, by oral gavage; the Em-L, Em-M, and Em-H groups were administered 8.75, 17.5, and 35 mg/kg emodin dissolved in a 0.5% sodium carboxy-methyl-cellulose solution (prepared to contain emodin at 5 g/L), respectively, by oral gavage, once daily. The emodin doses were determined based on the LD50 [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…The MG and CG groups were administered saline and 0.13 mg/kg ciprofloxacin, respectively, by oral gavage; the Em-L, Em-M, and Em-H groups were administered 8.75, 17.5, and 35 mg/kg emodin dissolved in a 0.5% sodium carboxy-methyl-cellulose solution (prepared to contain emodin at 5 g/L), respectively, by oral gavage, once daily. The emodin doses were determined based on the LD50 [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…As the major connection between intestinal epithelial cells, the TJ proteins in intestinal mucosa have an important role in maintaining the intestinal mucosa's mechanical barrier integrity and functions [ 1 ]. Decreased expression of TJ proteins leads to the increase of intestinal permeability, thus facilitating the entry of pathogens and toxic substances into the body [ 31 33 ]. TNF- α may have a central role in the complex chain reaction of cytokine-mediated intestinal mucosal injury [ 21 , 22 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that emodin may significantly reduce the damage to the intestinal epithelial barrier in sepsis, inhibit intestinal barrier permeability and protect intestinal barrier integrity, by elevating expression levels of the TJ proteins: claudin-3, ZO-1 and occludin in cecal ligation and puncture (CLP) rats [110].…”
Section: Antimicrobial Activitymentioning
confidence: 99%